Combined effects of pollution and bacterial infection in Sabella spallanzanii (Gmelin, 1971) - M. Dara; F. Bertini; C. La Corte; L. Bisanti; M. Staropoli; J. Vizioli; D. Parrinello; M. Cammarata; M. G. Parisi (The European Zoological Journal)
Sabella spallanzanii is a Mediterranean tube-dwelling polychaete living in shallow water. Here we evaluate its ability to respond to individual and combined treatments of methylmercury exposure and Escherichia coli challenge – two typical stressors of the eutrophic environment populated by the animal. Methylmercury is one of the most dangerous and toxic pollutants in marine environments, capable of bioaccumulating and being biomagnified within the food web with consequences for marine organisms. Here, the enzymatic and immune responses of Sabella spallanzanii have been investigated after exposure to methylmercury, along with the combined impacts of E. coli infection. Fan worms were subjected to four different treatments: control conditions (buffer injection); E. coli injection; CH3HgCl exposure combined, or not, with E. coli injection. Electrophoresis was performed to highlight possible alterations in protein patterns, differentially expressed upon bacterial and pollution challenges. Furthermore, enzymatic activities related to immune and physiological responses were assessed in whole body extracts. Our findings reveal the impact of methylmercury on the immunomodulation of S. spallanzanii, particularly in relation to oxidative stress and inflammatory markers. Each treatment led to a modulation of all the tested enzymatic activities, and the combined responses drastically reduced lysozyme activity.